Seasonal intensification of oxygen minimum zone: linking Godavari River discharge to fall hypoxia in the Bay of Bengal - Sreejith, K. S.; Sarma, V. V. S. S.; Pentakota, Sreenivas; Feba, F.; Hoteit, Ibrahim; Ashok, Karumuri (Frontiers in Marine Science, 2024)
Introduction This study investigates the biogeochemical impact of Godavari River discharge (GRD) on the Bay of Bengal (BoB), focusing on the formation of an intense and shallow oxygen minimum zone (OMZ) near the river mouth during the fall season. Unlike the BoB’s typical intermediate-depth OMZ, this subsurface (~40-200 m) phenomenon is attributed to the interplay of GRD-driven nutrient enrichment, coastal upwelling, enhanced productivity, and subsequent organic matter decomposition. Data and Methods Our analysis using the Biogeochemical-Argo floats and World Ocean Atlas 2018 data reveals that a clear shoaling and intensification of the OMZ in the fall season. Further, a comparative analysis at two geographically distinct locations highlighted the pivotal role of GRD. Results, Discussion, and Implications The location directly influenced by GRD exhibited significantly higher chlorophyll-a blooms, net primary production during the southwest monsoon, and pronounced oxygen consumption during the fall compared to the other. Our analysis suggests that GRD fuels primary productivity, leading to organic matter abundance and intense oxygen depletion in the subsurface layers, driving the observed shallow OMZ. Understanding the complex interplay between GRD, stratification, upwelling, and biogeochemical processes is crucial for predicting the impact of altered riverine inputs on coastal ecosystems, greenhouse gas emissions, and the overall health of the coastal BoB.